Practice Trends and Job Satisfaction of Dental Therapists in Canada: Results from a National Survey - Mohmmad Saad Khawer; Trish Goulet; Doug Brothwell; Keith Da Silva (International Journal of Circumpolar Health)
The objective of this research was to evaluate the practice trends, clinical services and job satisfaction of dental therapists in Canada. Licenced Canadian dental therapists were recruited to participate in this cross-sectional study. A total of 124 dental therapists completed the survey (~68% response rate), with 57.3% of respondents being over the age of 50. Most respondents were actively engaged in full-time clinical practice in private dental offices. Indigenous dental therapists were significantly more likely to work outside of private dental offices providing care for Indigenous communities. Just over half of respondents were compensated by an annual salary, with the highest proportion of full-time practitioners earning between $75,000 and $99,000 per year. Dental therapists who were active in clinical practice performed a wide range of preventive, diagnostic, and treatment services consistent with their scope of practice. This research demonstrates that Canadian dental therapists are highly engaged and satisfied with their profession. Dental therapists can facilitate improved access to oral health care in less accessible areas of Canada; however, compensation packages and incentives to work in these less accessible areas must be addressed, as well as legal and regulatory requirements to ensure that dental therapists are licenced providers throughout Canada.